Pathways from women's group-based programs to nutrition change in South Asia: A conceptual framework and literature review - Kumar, Neha; Scott, Samuel P.; Menon, Purnima; Kannan, Samyuktha; Cunningham, Kenda; Raghunathan, Kalyani; Quisumbing, Agnes R. (Elsevier, 2018)
Improving the nutritional status of women and children in South Asia remains a high public health and development priority. Women's groups are emerging as platforms for delivering health- and nutrition-oriented programs and addressing gender and livelihoods challenges. We propose a framework outlining pathways through which women's group participation may facilitate improvements in nutrition. Evidence is summarized from 36 studies reporting on 24 nutritional indicators across infant and young child feeding (IYCF) practices, intake/diet, and anthropometry. Our findings suggest that women's group-based programs explicitly triggering behavior change pathways are most successful in improving nutrition outcomes, with strongest evidence for IYCF practices. Future investigators should link process and impact evaluations to better understand the pathways from women's group participation to nutritional impact.